Empowering Women in the Transmission of the Qur'anic Traditions: A Case Study of the Traditions Program at STIU Wadi Mubarak Bogor - Muhammad Azizan Fitriana; Faldi Naviz Suardi (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to analyze the process of taḥammul (acquisition) of Qur’anic sanad among female students, examine the genealogy of the sanad they possess, identify the role of women in preserving Qur’anic sanad, and formulate strategies for developing an inclusive sanad program at STIU Wadi Mubarak Bogor. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document analysis involving program administrators, sanad instructors, female students, and relevant sanad documents. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The findings reveal that the taḥammul process is carried out through several stages, including participant selection, talaqqi, musyafahah, memorization recitation (‘arḍ), reinforcement of mutūn (classical texts), sanad examination, and the granting of sanad certification (ijazah). The genealogy of the female students’ sanad was found to be continuously connected (muttasil) to the Prophet Muhammad (PBUH) through the transmission of Hafṣ ‘an ‘Āṣim, providing strong scholarly and spiritual legitimacy. The study also demonstrates that women play significant roles as recipients of sanad, Qur’anic teachers, guardians of scholarly authority, agents of knowledge transmission, and contributors to the regeneration of Qur’anic education. To strengthen the sustainability of the program, the study proposes four main strategies: strengthening an adab and sanad based curriculum, developing flexible learning models, enhancing the competencies of female instructors, and reinforcing institutional support. These findings indicate that sanad programs can serve as an effective instrument for preserving the authenticity of Qur’anic transmission while simultaneously empowering women within the contemporary Islamic scholarly tradition.